Flexible electrically conductive films based on nanofibrillated cellulose and polythiophene prepared via oxidative polymerization - Dias, Otavio Augusto Titton; Konar, Samir; Leão, Alcides Lopes [UNESP]; Sain, Mohini (Elsevier, 2019)
Industrial ecology, sustainable manufacturing, and green chemistry have been considered platform‐based approaches to the reduction of the environmental footprint. Recently, nanofibrillated cellulose (NFC) has gained significant interest due to its mechanical properties, biodegradability, and availability. These outstanding properties of NFC have encouraged the development of a more sustainable substrate for electronics. In this context, the combination of NFC and conductive polymers may create a new class of biocomposites to be used in place of conventional electronics which are not optimally designed for use in flexible and mechanically robust devices. In this study, polythiophene was grafted onto nanocellulose surface at appropriate reaction times to obtain a strong, flexible, foldable films with capacity for electrical conductivity. Nanocomposites films were synthesized by a one-step reaction in which a 3-methyl thiophene monomer was oxidatively polymerized onto nanocellulose backbone. The nature of the fabricated NFC films changed from insulator to semiconductor material upon oxidative polymerization.
Keywords: Conductive polymer; Grafting polymerization; Nanocellulose; Thin films